Exploring patient interpretation of an orthosis adherence checklist: A cognitive interview study - Marjan Saeedi; Joy Christine MacDermid; Louis Ferreira; Sahar Johari; Mike Szekeres (PLoS ONE, 2026)
Upper extremity orthoses are commonly used in rehabilitation to reduce pain, improve alignment, and support return to daily activities. These benefits depend on regular and correct use, yet adherence is influenced by personal, environmental, and device-related factors. Although a checklist of adherence-related items has been developed based on clinician expertise, it has never been evaluated by patients. Understanding how patients interpret these items is essential before the checklist can inform development of a patient-reported outcome measure (PROM) to support adherence. The aim of this study was to explore how people with lived experience of upper extremity pain and disability using upper extremity orthoses understand and respond to the items in an adherence checklist, and to identify areas requiring improvement. Cognitive interviews were conducted with adults who had used an upper extremity orthosis to evaluate a clinician-developed adherence checklist. Using a think-aloud approach and follow-up questions, participants described how they interpreted each item and selected responses. Directed content analysis was used to categorize interpretation issues related to clarity, relevance, and reference point. Thirteen participants were interviewed. Most items were interpreted as meaningful and easy to answer. However, several terms were perceived as confusing or overly technical, including “customizability,” “aesthetics,” and “undue strain.” Interpretation of some items depended on context; for example, “breathability” varied with weather, and “flexibility” depended on the intended function of the orthosis. “Affordability” was not relevant for many participants, indicating the need for a “Not applicable” response option. When asked about adherence, participants commonly described following instructions rather than a broader, multidimensional concept. Participants valued the intent and content of the items. Cognitive interviewing identified ways to improve wording, add contextual cues, and refine response options to better reflect diverse experiences. These refinements will support development of a patient-centred outcome measure for assessing adherence to upper extremity orthoses.